Rift Valley fever virus seroprevalence among ruminants and humans in northeast Kenya - Lindahl, Johanna F.; Njeru, I.; Karanja, J.; Grace, Delia; Bett, Bernard K. (International Livestock Research Institute, 2016)
Rift Valley fever (RVF) is a zoonotic vector-borne disease present in much of Africa, and the Arabic peninsula. During outbreaks, the case fatality is high in young ruminants and there may be abortion storms, human disease is usually mild but some may suffer fatal hemorrhagic fever. Outbreaks in East Africa occur after periods of heavy prolonged rains, such as during El Niño southern oscillations, which lead to a sudden increase in the number of vectors hatched. Between outbreaks, there are indications that the virus is still circulating in some ecologies. Kenya has suffered repeated serious outbreaks of RVF, with high morbidity in humans and animals, and also severe economic consequences. In the northern of Kenya, a hot spot for RVF outbreaks, there are continuous expansions of irrigation schemes, which enable the societies to be less susceptible to droughts. However, there are concerns that the increased irrigation would provide more vector breeding grounds, and thus cause people living close to be more exposed to vector-borne diseases. In this study, 1117 serum samples were collected from humans in the age 5-90 years old, in the irrigated area, a riverine area, and the close-by district where people are fully depending on pastoralism. Samples were tested with a competitive ELISA detecting both IgM and IgG antibodies. Overall seroprevalence was 21.9%, and univarible analyses could find no difference between the three areas, but men were found to be significantly more seropositive than women (26.2 and 18.8% respectively, p=0.004). Ruminants (sheep, goats, and cattle) were also sampled within the irrigation. A total of 1997 animals were sampled, and tested with the same ELISA as the human samples. Overall seroprevalence was 25.6%, with no difference between the seroprevalences in goats, sheep and cattle. Juveniles had lower seroprevalence rates than adults, 12.3% compared to 30.2% (p<0.001). Since the last outbreak occurred in 2006-2007, juveniles could not have been infected during that outbreak. In conclusion, the study confirms that RVF can be circulating in ruminants between epidemics in irrigation schemes. However, the human sampling did not show any evidence that living in irrigation schemes would make people more exposed, although the exposure detected here is cumulative and longitudinal surveys may be more suitable to detect differences in infection rates.